Lack of clinically meaningful anatomical variations in bone marrow apparent diffusion coefficient in diffuse pattern myeloma allows untargeted sampling to confirm disease burden. Issue 4 (2020) - Keeling, Archie; O'Connor, Simon; Boyd, Kevin; Kaiser, Martin; Blackledge, Matthew; Koh, Dow-Mu; Messiou, Christina
No abstract available